Synthesis of β-Lactams via Enantioselective Allylation of Anilines with Morita–Baylis–Hillman Carbonates - Zi, You; Lange, Markus; Schüler, Philipp; Krieck, Sven; Westerhausen, Matthias; Vilotijevic, Ivan (Synlett, 2020)
Enantioenriched β-lactams are accessed via enantioselective allylation of anilines with Morita–Baylis–Hillman carbonates followed by a base-promoted cyclization. The resulting 3-methyleneazetidin-2-ones are amenable to diastereoselective functionalization to produce analogues of biologically active β-lactams. The use of nearly equimolar quantities of the starting materials make this method efficient and straightforward.
Keywords: β-lactams; allylic substitution; allylation; Lewis base catalysis